Sundaic elephants prefer habitats on the periphery of protected areas. Issue 12 (17th October 2022) - de la Torre, J. Antonio; Cheah, Cheryl; Lechner, Alex M.; Wong, Ee Phin; Tuuga, Augustine; Saaban, Salman; Goossens, Benoit; Campos‐Arceiz, Ahimsa
Abstract: Protected areas (PAs) are a cornerstone of global conservation strategies. PAs, however, are not equally effective for all threatened taxa, and it is important to understand taxa‐specific effectiveness of PAs networks. In this study, we evaluate the role of the PAs network on the protection of Asian elephants Elephas maximus and their habitats in Southeast Asia's Sundaic region. Since Asian elephants tend to prefer secondary forests or forest gaps, we predicted that PAs would not represent the species preferred habitats. We conducted the most comprehensive analysis of Asian elephant space and habitat use to date through home range estimations and step selection function analyses using over 600, 000 Global Positioning System locations from 102 different elephants from Peninsular Malaysia and Borneo. Our results revealed important similarities in the habitat use of elephants in both regions, with both females and males in Peninsular Malaysia and Sabah preferring secondary forest, forest gaps and areas of regrowth and new plantations. Our results supported our prediction that PAs do not represent Asian elephants' preferred habitats, since for most of the elephants, more than half of their ranges were outside PAs and the probability of selection values for both sexes in both geographical areas were lower inside than outside the PAs. Synthesis and applications. Our analysis suggests that conservation strategies need to acknowledge that the long‐term survival of Asian elephants in the Sundaic region relies on our capacity to promote human–elephant coexistence at the boundaries of PAs. We advocate that Asian elephant conservation strategies should be based on the following three key points: (1) large PAs with core areas where elephants can find safety and potentially survive in the long term; (2) promoting connectivity among PAs using a system of wildlife corridors; and (3) effective human–elephant conflict management outside PAs. Abstract : Our analysis suggests that conservation strategies need to acknowledge that the long‐term survival of Asian elephants in the Sundaic region relies on our capacity to promote human–elephant coexistence at the boundaries of PAs. We advocate that Asian elephant conservation strategies should be based on the following three key points: (1) large PAs with core areas where elephants can find safety and potentially survive in the long term; (2) promoting connectivity among PAs using a system of wildlife corridors; and (3) effective human–elephant conflict management outside PAs.